Profile of Breast Cancer Patients at Dr. Moewardi Surakarta Period March 2016 - March 2018 - Randi Dwiyanto; Widyanti Soewoto (HM Publisher, 2021)
Introduction: Breast cancer is a heterogeneous disease caused by the interaction of genetic factors and environmental risk factors that lead to the accumulation of progressive genetic and epigenetic changes in breast cancer cells. The incidence of breast cancer in Indonesia is 11% of all cancer incidents. There are many factors that are thought to have an influence on the occurrence of breast cancer, including age, immunohistochemistry, and variable levels of first breast carcinoma at old age. Methods: A descriptive retrospective study by taking medical record data about breast cancer at the Dr. Moewardi General Hospital, Surakarta. at the Installation of Medical Records at the General Hospital DR. Moewardi Period February 2016 - February 2018. Results: According to the age group of 50 years, 162 patients (54%) and above who had a high risk and under 50 years group were 138 patients (46%). From the results of the study, breast cancer patients with grade 3 were found to be the most with 155 cases (51.67%). Hormonal receptor detection in breast cancer patients showed a high incidence of HER-2-negative patients as many as 172 patients (57.33%). The rest showed positive HER-2 results as many as 128 patients (42.67%). There was a high incidence of negative HER-2 as many as 172 patients (57.33%). The rest showed positive HER-2 results as many as 128 patients (42.67%). Positive HER-2 subtypes (ER-, PR-, HER2 +) were the most common cases, namely 128 cases (42.67%). The magnitude of the correlation (Phi and Cramer) produces the same number, while the contingency coefficient produces a smaller number. Conclusion: There is almost no relationship or there is a very weak relationship between age, immunohistochemistry, and variable rates of breast carcinoma, variable rates of breast carcinoma at the occurrence of metastases.